STUDENTS PERCEPTION ON CREATING VISUAL CULTURE ESSAY COLLABORATIVELY - Tamaela Ida Costansa (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
The objective of this research is to find out students perceptions towards the implementation of creating visual culture essay collaboratively. It is a qualitative research in which the data were collected through questionnaire and interview. Ten students from the German education study program of Language and Art Department at Teachers Training and Educational Science faculty of Pattimura University, Ambon, took active participation in designing visual culture essay collaboratively.Based on the topic on culture provided by the lecturer, the group worked at the planning and designing stages of the visual culture essay. Each member of the group prepare his/her drawing accompanied by a short description to contribute to the group’s visual essay. The research focuses on (1) students’ perceptions on creating visual culture essay collaboratively, namely the facts and challenges, (2) the assessment result of students’ design of visual culture essay. The research findings showstudents positive perceptions of the collaborative work. Moreover, the assessment result of their partly individual design ranges from ‘acceptable’ to ‘exemplary’, while the group’s visual culture essay is categorized as ‘acceptable’. Taking into consideration that this is the first time they designed a visual culture essay and designed it as a group, the result can be categorized as quite acceptable. When practiced on a regular basis undoubtedly the result will be quite an achievement